PERCERAIAN DINI: STUDI TERHADAP PUTUSAN PENGADILAN AGAMA PEKALONGAN TAHUN 2013 - Ahmad Tugabus Surur; Hanik Rosyidah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
This research aims to investigate the current phenomenon of divorce by young spouses who have short marriage, to discover the underlying factors causing early divorce, and to know how the judge resolves the case of early divorce. The word